Crack-cocaine users have less family cohesion than alcohol users - Marchi, Nino C. (Braz J Psychiatry, 2017)
OBJECTIVE: Many studies correlate characteristics of family functioning and the development of drug addiction. This study sought to evaluate and compare the family environment styles of two groups of psychoactive substance users: 1) alcohol-only users and 2) crack-cocaine users. METHODS: Three hundred and sixty-four users of alcohol, crack-cocaine, and other drugs, recruited from research centers in four Brazilian capitals participated in this study. Subjects were evaluated through the Family Environment Scale and the Addiction Severity Index, 6th version (ASI-6). ASI-6 t-scores were compared by analysis of variance (ANOVA) and post-hoc tests. A final model was obtained using a logistic regression analysis. All analyses were adjusted for partner, age, and psychiatric t-score. RESULTS: We found a significant difference between groups in the cohesion subscale (p = 0.044). The post-hoc test revealed a difference of 1.06 points (95%CI 0.11-2.01) between groups 1 (6.45±0.28) and 2 (5.38±0.20). No significant between-group differences were observed in the other subscales. However, categorical analyses of variables regarding family dynamic showed that crack users more often reported that sometimes people in their family hit each other (30.4% vs. 13.2%, p = 0.007) and that people in their family frequently compared each other regarding work and/or school achievement (57.2% vs. 42.6%, p = 0.041). CONCLUSION: These results suggest that families of crack-cocaine users are less cohesive than families of alcohol users. This type of family environment may affect treatment outcome, and should thus be adequately approached.